3D bioprinting and Rigenera® micrografting technology: A possible countermeasure for wound healing in spaceflight - Aliberti, Flaminia; Paolin, Elisa; Benedetti, Laura; Cusella, Gabriella; Ceccarelli, Gabriele (Frontiers in Bioengineering and Biotechnology, 2022)
Plant and animal life forms have progressively developed mechanisms for perceiving and responding to gravity on Earth where homeostatic mechanisms require feedback. Lack of gravity, as in the International Space Station (ISS), induces acute intra-generational changes in quality of life. These include reduced bone calcium levels and muscle tone, and provoking skin deterioration. All these problems reduce work efficiency and quality of life of humans not only during exposure to microgravity (µG), but also after returning on Earth. This paper discusses forthcoming experiments required, under gravity and µG conditions to ensure effective and successful medical treatments for astronauts during long-term space missions, where healthcare is difficult and not guarantee.